2015
DOI: 10.1590/1413-785220152306115026
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients submitted to surgical treatment of idiopathic scoliosis

Abstract: OBJECTIVE: To evaluate quality of life, using the SF-36, in patients with adolescent idiopathic scoliosis (AIS) who un-derwent surgery for deformity correction, comparing the results in the pre-and post-operative period. METHODS: We evaluated 29 patients, 24 female, mean age 14.5 years, all patients had measurement of Cobb angle greater than 50º, and responded to the SF-36 questionnaire preope-ratively and on average two years after surgery. RESULTS: There was improvement in all eight domains studied by the SF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…Pain is a symptom commonly experienced following surgery due to tissue damage 4. Idiopathic scoliosis surgery (posterior spinal fusion), a common orthopedic surgery in children and adolescents, is a surgical procedure to correct spinal deformities, which generates high levels of pain 5. This major invasive surgical procedure entails considerable nociceptive input in a highly innervated area, rendering the pain assessment and management an important challenge for clinicians and patients postoperatively 6,7…”
Section: Introductionmentioning
confidence: 99%
“…Pain is a symptom commonly experienced following surgery due to tissue damage 4. Idiopathic scoliosis surgery (posterior spinal fusion), a common orthopedic surgery in children and adolescents, is a surgical procedure to correct spinal deformities, which generates high levels of pain 5. This major invasive surgical procedure entails considerable nociceptive input in a highly innervated area, rendering the pain assessment and management an important challenge for clinicians and patients postoperatively 6,7…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have sought out to assess how mental health changes in patients with AIS over time, [ 2 , 3 ] and some have found that change to be associated with curve severity, treatment type, and duration of treatment. [ 5 ] These studies of patients with AIS have used assessments such as the Scoliosis Research Society-22r Patient Questionnaire (SRS-22) [ 6 , 7 ] and other health-related quality of life assessments, [ 3 , 8 ] but none have used as detailed of a measure as the BASC-2 Assessment. The purpose of this study was to assess the behavioral and emotional functioning of AIS patients with differing treatment protocol over a 2-year period using the BASC-2 patient and parent surveys.…”
Section: Introductionmentioning
confidence: 99%
“…EOS is classified according to the age of the patient at the start of the deformity as early (0–5 years old) or late (> 5 years old) onset scoliosis [ 3 5 ]. Surgery in patients with EOS aims to correct the deformity avoiding complications improving the patient’s long-term health-related quality of life [ 6 9 ]. Concomitant neuromuscular, congenital, or syndromic scoliosis are associated with greater morbidity and mortality [ 3 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%